2013
DOI: 10.1371/journal.pone.0062779
|View full text |Cite|
|
Sign up to set email alerts
|

Immediate Ecological Impacts of the 2011 Tohoku Earthquake Tsunami on Intertidal Flat Communities

Abstract: Following the Great East Japan Earthquake in 2011, a large tsunami developed and struck the Pacific coast of eastern Japan. To assess the immediate impacts of the tsunami on coastal communities, changes in taxon composition and richness of macrobenthic animals before and after the tsunami were examined at nine intertidal flats in Sendai Bay and the Sanriku Ria coast. The results showed that 30–80% of taxa indigenously inhabiting intertidal flats disappeared after the tsunami. Among animal types, endobenthic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 18 publications
3
54
0
Order By: Relevance
“…Large differences within a small spatial scale were also reported in the impact assessment of the 2004 tsunami along the Andaman Sea coast of Thailand (Whanpetch et al 2010). Similar tsunami impact assessments have been ongoing by various marine scientists and fisheries researchers who have been studying the areas since before the disaster happened (Urabe et al 2013;Takami et al 2013). Mate analysis incorporating these individual studies across a large spatial extent and diverse environmental gradients provide promising ways to understand general characteristics of how the tsunami's impacts and subsequent recovery processes varied.…”
Section: Disaster Resilience and Coastal Ecologymentioning
confidence: 75%
“…Large differences within a small spatial scale were also reported in the impact assessment of the 2004 tsunami along the Andaman Sea coast of Thailand (Whanpetch et al 2010). Similar tsunami impact assessments have been ongoing by various marine scientists and fisheries researchers who have been studying the areas since before the disaster happened (Urabe et al 2013;Takami et al 2013). Mate analysis incorporating these individual studies across a large spatial extent and diverse environmental gradients provide promising ways to understand general characteristics of how the tsunami's impacts and subsequent recovery processes varied.…”
Section: Disaster Resilience and Coastal Ecologymentioning
confidence: 75%
“…The March 2011 disasters have had enormous environmental impacts [Kontar at al., 2014;Ministry of Environment, 2017;NASA, 2011;Urabe et al, 2013;UNSCEAR, 2014;WWF, 2013].…”
Section: Environmental Impactmentioning
confidence: 99%
“…For instance, in Mangokuura lagoon, Ishinomaki City, the ground was seen to have subsided by about 0.9-1.5 meters, becoming muddy as sludge accumulated, distribution area of the Zostera was drastically reduced, and their population growing from the coast up to about 100 meters out at sea was exterminated. The study of Sendai Bay and the Sanriku Ria coast showed that 30-80% of taxa indigenously inhabiting intertidal flats disappeared after the tsunami [Urabe et al, 2013]. Among animal types, endobenthic and sessile epibenthic animals were more vulnerable to the tsunami than mobile epibenthic animals like shore crabs and snails.…”
Section: Environmental Impactmentioning
confidence: 99%
“…Many studies conducted after the tsunami have focused on the ecological impacts caused by the 2011 tsunami and have demonstrated drastic changes in species composition and abundance of fish and benthic communities at various sites (Masuda 2012(Masuda , 2013Miura et al 2012;Nakayama et al 2013;Seike et al 2013;Urabe et al 2013). The tsunami similarly affected riverine macroinvertebrate communities far upstream from the river mouth during inundation (Watanabe et al 2014).…”
Section: Introductionmentioning
confidence: 99%